2003
DOI: 10.1029/2003jd003471
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for slowdown in stratospheric ozone loss: First stage of ozone recovery

Abstract: [1] Global ozone trends derived from the Stratospheric Aerosol and Gas Experiment I and II (SAGE I/II) combined with the more recent Halogen Occultation Experiment (HALOE) observations provide evidence of a slowdown in stratospheric ozone losses since 1997. This evidence is quantified by the cumulative sum of residual differences from the predicted linear trend. The cumulative residuals indicate that the rate of ozone loss at 35-45 km altitudes globally has diminished. These changes in loss rates are consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
346
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(377 citation statements)
references
References 62 publications
(78 reference statements)
26
346
1
Order By: Relevance
“…Thus, we should pay more attention to the examination of sources of the cloud long-term and short-term variations. In case of slowdown of the total ozone trend over the Northern Hemisphere's mid-latitudes and the anticipated the ozone recovery (WMO, 2003, Newchurch et al, 2003, clouds will appear as the most important modulator of the UV radiation both over long-and short-time scales during the next decades.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we should pay more attention to the examination of sources of the cloud long-term and short-term variations. In case of slowdown of the total ozone trend over the Northern Hemisphere's mid-latitudes and the anticipated the ozone recovery (WMO, 2003, Newchurch et al, 2003, clouds will appear as the most important modulator of the UV radiation both over long-and short-time scales during the next decades.…”
Section: Discussionmentioning
confidence: 99%
“…[59] Different to other current studies [e.g., Reinsel, 2002;Reinsel et al, 2002Reinsel et al, , 2005Newchurch et al, 2003;Steinbrecht et al, 2004;Weatherhead and Andersen, 2006;Brunner et al, 2006a] our analysis is not focused on trends and possible changes of them.…”
Section: Trendsmentioning
confidence: 99%
“…However, the ratification of the Montreal Protocol and its amendments prevented the EESC from growing linearly after 1995. More recently other concepts were developed to study the effectiveness of the Montreal protocol [e.g., Reinsel, 2002;Reinsel et al, 2002Reinsel et al, , 2005Newchurch et al, 2003;Steinbrecht et al, 2004;Weatherhead and Andersen, 2006;Brunner et al, 2006a], which is out of scope of the presented analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Newchurch et al 2003;Angell and Free 2009;Eyring et al 2010;Krzyścin 2010;Zhang et al 2014;Chipperfield et al 2017). However, some studies have shown that stratospheric ozone concentrations over different regions along the same latitude exhibit different recovery rates.…”
Section: Introductionmentioning
confidence: 99%